Heart failure: Same-hospital vs. different-hospital readmission outcomes. (1st March 2019) - Lahewala, Sopan; Arora, Shilpkumar; Tripathi, Byomesh; Panaich, Sidakpal; Kumar, Varun; Patel, Nirali; Savani, Sejal; Dave, Mihir; Varma, Yash; Badheka, Apurva; Deshmukh, Abhishek; Gidwani, Umesh; et al.
Abstract: Background: Heart Failure (HF) is a major driver of the readmissions/penalties in the US. Although extensive literature on rehospitalization attributed to HF, studies to compare outcomes for same-hospital vs. different-hospital readmissions are sparse. Methods: Nationwide Readmission Database from 2010 to 14 utilized for HF-related hospitalization using appropriate ICD-9-CM diagnostic codes. 30-day readmissions were classified into two groups: same-hospital and different-hospital. A comparative analysis was conducted focusing on: in-hospital mortality, length of stay (LOS) and hospitalization cost. Hierarchical two-level modeling and propensity score matching utilized to adjust confounders. Results: 715, 993 HF readmissions were identified, of which 21.3% were readmitted to different-hospital. Elderly, females, patients with higher co-morbidities and higher median household income were less likely to be readmitted to different-hospital. Index hospitalizations in a teaching hospital and/or larger hospital were associated with reduced different-hospital readmissions. Readmissions to the different hospital were associated with higher in-hospital mortality (7.7% vs. 6.6%, p < 0.001), higher resource utilization (LOS:7.5 days vs. 6.1 days, p < 0.001 and Cost: 22, 602 vs. 13, 740, p < 0.001) after adjusting for propensity score match. Similar results were observed with propensity score matching of multiple high-risk subgroups. Conclusion: Resources should be directed towards minimizing different-hospital HF readmissions to improve patient outcomes by identifying the vulnerable subgroup and further tailoring in-hospital and post-discharge care. Highlights: Heart failure outcomes for same vs. different hospital readmission are seldom studied. Higher household income, elderly, females less likely readmitted to different-hospital. Readmissions to the different hospital were associated with higher in-hospital mortality. Different hospital readmissions were associated with higher resource utilization.